Evaluation of energy and performance of explosives - Vágenknecht, Jiří; Vávra, Pavel (Univerzita Pardubice, 2002)
The paper presents an analysis of problems of evaluation of the energy content and performance of high explosives. A description is mentioned of the Cylinder test as a modern experimental method for obtaining more complex and versatile information necessary for this evaluation. The calculations from JWL state equation have been used to document differences in mechanisms of energy release by various explosives during detonation.
Keywords: výbušniny; energetické bilance; detonační parametry; testovací metody